Letter from Tomas O'Morain to T. J. Hickey - Anti-Partition League, APL; O'Morain, Tomas (1939)
Typescript letter dated 10 Bealtaine (May) 1939, to T J Hickey, from Tomas O'Morain, about the question of salary, with manuscript P.S. at end of letter.